Herlufsholm-samlingen på Syddansk Universitetsbibliotek og forskningspotentialet – om forskellige fund af fragmenter - Holck, Jakob Povl (Studier i Nordisk, 2022)
The Herlufsholm Special Collection at the University Library of Southern Denmark in Odense contains many hitherto unknown medieval manuscript fragments and other spectacular library materials. These items constitute a relatively uncatalogued collection, and efforts are now being made to find, identify, register, and digitize them for online availability. This article emphasizes the great scholarly potential of the Herlufsholm Special Collection in various fields of research and gives examples of some of the newly found treasures. It lists the interdisciplinary scientific opportunities and describes modern technological methods for the speedy recovery of ancient texts/works and their contexts.